Dysregulation of Ephrin receptor and PPAR signaling pathways in neural progenitor cells infected by Zika virus. Issue 1 (1st January 2020) - Thulasi Raman, Sathya N.; Latreille, Elyse; Gao, Jun; Zhang, Wanyue; Wu, Jianguo; Russell, Marsha S.; Walrond, Lisa; Cyr, Terry; Lavoie, Jessie R.; Safronetz, David; Cao, Jingxin; Sauve, Simon; et al.
ABSTRACT: Zika virus (ZIKV) infection is a serious public threat with cases reported in about 70 countries and territories. One of the most serious consequences of ZIKV infection is congenital microcephaly in babies. Congenital microcephaly has been suggested to result from infection of neural progenitor cells (NPCs) in the developing fetal brain. However, the molecular and cellular mechanisms underlying microcephaly development remains to be fully elucidated. In this study, we employed quantitative proteomics to determine protein expression profile that occur during viral replication in NPCs. Bioinformatics analysis of the protein expression changes resulted in the identification of a wide range of cell signaling pathways. Specifically, pathways involved in neurogenesis and embryonic development were markedly altered, along with those associated with cell cycle, apoptosis, lipid metabolism and oxidative stress. Notably, the differential regulation of Ephrin Receptor and PPAR signaling pathways, as revealed by quantitative proteomics and validated by qPCR array, underscores the need to explore these pathways in disease development. Collectively, these results indicate that ZIKV-induced pathogenesis involves complex virus-host reactions; the findings reported here could help shed light on the mechanisms underlying ZIKV-induced microcephaly and ZIKV replication in NPCs.